DEVELOPMENT LEARNING MEDIA â€œSTUDY ROOMâ€ BASED OF E-LEARNING USING GOOGLE CLASSROOM ON SOCIAL STUDIES SUBJECTS IN ELEMENTARY SCHOOL - Rosi Tri Handayani; Mahilda Dea Komalasari (Universitas PGRI Yogyakarta, 2022)
This study aims to determine the feasibility of developing learning media â€œstudy roomâ€ based of e-learning using google classroom on social studies subjects in elementary schoolfor class IV SD Negeri Bengbulang 02 through student responses and teacher responses to learning media â€œstudy roomâ€, then knowing the effectiveness of learning media â€œstudy roomâ€ in improving results. students' learning in the cognitive domain in social studies subjects for class IV SD Negeri Bengbulang 02. The research was conducted using the Research and Development (R&D) method. The sample used is the fourth grade students of SD Negeri Bengbulang 02 with a total of 20 students. The development procedure carried out follows the steps developed by Dick and Carry with the ADDIE step. Data collection techniques used are interviews, questionnaires, and tests. The data analysis techniques used were descriptive quantitative statistics, and quantitative inferential statistics which included prerequisite tests and paired sample t-tests. The results of this study are the Study Room learning media used in social studies subjects for class IV SD Negeri Bengbulang 02 with the feasibility of material experts, student responses and teacher responses, scores of 72, 119 and 48 categories are very good, respectively. The results of the student assessment with an average pretest score of 70.29 and posttest value of 99.12. Based on the results of the paired t-test in accordance with the test criteria, namely H0 is accepted if tcount ttable at the significance level = 0.05 and db= (n-1), for other t values H0 is rejected, it is known that the value of sig (2- tailed) of 0.001 0.05, then Ha is accepted and it is stated that there is a significant difference in the pretest and posttest values. The effectiveness of the e-learning based study room learning media using google classroom is seen through the students' pretest average score of 70.29 and the posttest average value of 99.12, so the students' posttest scores are greater than the students' pretest scores. Thus, it can be concluded that the learning media based on e- learning is effective on learning outcomes in the cognitive domain